Technical Writing @ SLCC (Open textbook library., 2020)
What is technical writing? You can think of it as writing about specialized topics or you could also think of it as using technology to communicate your ideas. A science lab report, a specification, a change order for building construction, or patient education materials–just to name a few–are all considered technical writing. Similarly if you design a webpage or a brochure this can also be considered technical writing. Academic writing, the writing you do for school, generally is informative or persuasive writing and usually only comes in a few different genres. In technical writing, on the other hand, one is often documenting what was done (such as a science experiment or auto repair invoice). Therefore the format of the writing is often as important as the content. This leads to an emphasis on usability and accessibility for your documents. Finally, although citing your sources is important in all writing, you will find that in some fields of technical writing, such as the sciences and engineering, it is one of the more important considerations of your writing.